1986
DOI: 10.1177/00220345860650011101
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulins and Innate Antimicrobial Factors in Whole Saliva of Patients with Insulin-dependent Diabetes Mellitus

Abstract: We analyzed the flow rate and composition of paraffin-stimulated whole saliva samples from 35 adult diabetic patients and their age- and sex-matched, non-diabetic, clinically healthy controls. All patients had insulin-dependent diabetes (IDDM) with a mean (+/- S.D.) duration of 14.0 +/- 9.1 years. The saliva analysis included the quantitation of total protein, amylase, immunoglobulins (isotypes A, G, and M), and the non-antibody, innate antimicrobial factors (lysozyme, lactoferrin, salivary peroxidase, myelope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
50
2
3

Year Published

1987
1987
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 22 publications
8
50
2
3
Order By: Relevance
“…13 Our results revealed that levels of salivary total protein were higher in IDDM group as compared to control group [ Table 1]. These results are in accordance with the previous studies done by Lopez 22 showed no significant difference between the diabetic patients and controls. This contradiction can be explained by the fact that the studies might have incorporated different methodology and metabolic control status of the patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…13 Our results revealed that levels of salivary total protein were higher in IDDM group as compared to control group [ Table 1]. These results are in accordance with the previous studies done by Lopez 22 showed no significant difference between the diabetic patients and controls. This contradiction can be explained by the fact that the studies might have incorporated different methodology and metabolic control status of the patients.…”
Section: Discussionsupporting
confidence: 88%
“…The elevated levels could be explained with abnormal binding of serum proteins to salivary gland basement membranes may be a reflection of increased permeability; this basement membrane permeability is often associated with diabetes which leads to increased passage of proteins, IgG, albumin, and polyvalent immunoglobulins from exocrine glands into their secretions. 22 The salivary flow rate in diabetes is also diminished which is related to salivary viscosity and foam. Viscosity otherwise called "spinbarkeit" and foam are reflected by the higher levels of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Lopez et al (9) reported higher urea and total protein salivary content in diabetic children than in controls. Conversely, a study on 35 adult insulin-dependent diabetics demonstrated that they did not show a decreased saliva concentration of several innate antimicrobial factors (lysozyme, lactoferrin, salivary peroxidase, myeloperoxidase) and that protein synthesis in salivary glands, as judged by amylase assays, was within the normal range (11). In the same study, higher amounts of immunoglobulin A (IgA) and IgG in diabetics with respect to controls were detected.…”
mentioning
confidence: 90%
“…Flow rate and composition of saliva are crucial for the maintenance of oral cavity health, and both have been found altered in diabetic subjects, although with contradictory findings. For instance, several studies reported a reduced resting salivary flow rate in adults and children who have type 1 diabetes with respect to healthy subjects (5-10), but it was also observed that stimulated saliva of diabetics and controls did not significantly differ (11,12). Total protein concentration of saliva was found either increased or not affected by the diabetic status.…”
mentioning
confidence: 95%
“…17 Brandtzaeg (1972) and found that there was significantly elevated IgA level in whole saliva of diabetic patients. 18,19 …”
Section: Jiaomrmentioning
confidence: 99%